Penetrating Atherosclerotic Ulcer of Aorta: A Giant Lurking in the Dark - Timala, Rabindra B; Sharma, Jyotindra; Pradhan, Siddhartha; Gautam, Navin Chandra (Nepalese Heart Journal, 2014)
Penetrating atherosclerotic ulcer is one of the acute aortic conditions, associated with high morbidity and mortality. Management option is often debated between conservative vs. surgical, with different data supporting each of the option. Here we present two case reports, managed conservatively. Nepalese Heart Journal | Volume 10 | No.1 | November 2013| Pages 57-60 DOI: http://dx.doi.org/10.3126/njh.v10i1.9748